Gdańsk - Kamienica Steffensa ([S.l. : s.n., 1945)
Przedstawia Złotą Kamienicę w Gdańsku, ok. 1960 r.
Data wg przedstawienia.
Keywords: Karty pocztowe -- Polska -- Gdańsk; Gdańsk (Polska) -- 1945-1970 -- karty pocztowe